Spatial Clustering of Termites but Not Fungi at Site‐Scale Drive Global Wood Decay Patterns - Donghao Wu; Chengjin Chu; Sebastian Seibold; Yuanyuan Luo; Nico Eisenhauer; Jérome Mathieu; Mingjian Yu (Global Change Biology, 2026)
Deadwood stores ~8% of global forest carbon, and termites and fungi are its primary decomposers—organisms whose activities are likely to intensify under global warming. Yet it remains unclear how their site‐scale spatial self‐organization—whether clustered or overdispersed—varies with global change stressors and shapes global wood decomposition patterns. Leveraging a global experiment, we find that increasing termite spatial occupancy is associated with more clustered patterns of decomposition rates, whereas higher fungal spatial occupancy is associated with more overdispersed patterns. Notably, temperature more strongly increases termite occupancy and thus indirectly contributes to clustered patterns, while anthropogenic pressure more strongly and directly promotes overdispersed patterns by reducing termite occupancy. Termite‐driven clustering is positively associated with site‐scale decomposition rates, contributing as much to global variation as termite occupancy and temperature. In contrast, fungi‐driven overdispersion slightly decelerates site‐scale decomposition rates via weakening the positive effects of fungal occupancy. Our study highlights that the within‐site spatial patterns of decomposer activities are important drivers of global wood decomposition. Under global warming, termite clustering and range expansion may contribute to accelerating deadwood decomposition. However, human disturbances slow decomposition by disrupting termites' self‐organization, adding uncertainty to the fate of deadwood carbon pools.